Draft Genome Sequence of Plant-Growth-Promoting Rhizobacterium Serratia fonticola Strain AU-AP2C, Isolated from the Pea Rhizosphere - Devi, Usha (American Society for Microbiology, 2013)
Plant health can be augmented by plant-growth-promoting rhizobacteria (PGPR) that confer biofertilizer, phytostimulation, and biocontrol activities. Herein, we provide the high-quality draft genome sequence of Serratia fonticola strain AU-AP2C, a Gram-negative motile PGPR of the pea plant, conferring phosphate solubilization, ammonia production, and antifungal activity against Fusarium sp. The 4.9-Mb genome contains genes related to plant growth promotion and synthesis of siderophores.